Japanese monetary policy and household saving - Karl-Friedrich Israel; Tim Sepp; Nils Sonnenberg (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2021)
This paper analyzes the impact of monetary policy on household saving in Japan between 1993 and 2017. Using annual data from the Japan Panel Survey of Consumers it is shown that monetary expansion has contributed to a widening gap in households' net saving through an adverse effect on the volume of saving of non-academic households. In contrast, households with at least one academic tend to be able to compensate these adverse effects of monetary expansion or can even benefit from it. The paper documents how inequality in terms of the ability to build up wealth has increased in Japan over the past decades. The statistical analysis controls for household size as well as potential spatial effects in the transmission mechanism of monetary policy on household saving.
Keywords: D31; D63; E52; E58; 330; Japan; interest rate; monetary policy; household saving; inequality